MENINJAU SKEPTISISME PROFESIONAL AUDITOR, INDEPENDENSI DAN RED FLAGS TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (STUDI KASUS INSPEKTORAT KABUPATEN PONOROGO DAN MADIUN) - Susilawati, Desi; Utami, Tri; Indriani, Afif Aprilia (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2022)
This study aims to analyze the Professional Auditor's Skeptic Independence, and Red Flags on the Auditor's Ability to Detect Fraud. The sample a in this study are auditors who worked at the Inspectorate of Ponorogo and Madiun Regencies conssist of 31 auditors.This research uses purposive sampling method by distributing questionnaires with a Likert scale and which has met the validity and reliability requirements. Data analysis and hypothesis testing using multiple linear regression. The results of multiple linear analysis indicate that the variable auditor professional skepticism has a significant effect on the ability of auditors to handle fraud. Meanwhile, the red flag variable does not have a significant effect on the ability of auditors to detect fraud. Consequently, this study’s implication is Auditor must always uphold the attitude of professional skepticism and independence in every audit action andpProcedures because auditors who have this attitude will affect the auditor's ability to detect fraud.